DESKRIPSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL-SOAL STOIKIOMETRI DI KELAS X IPA SMA ISLAM BAWARI - Hidayatullah Hidayatullah; Hairida Hairida; Lukman Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The aims of this research was to describe student errors when solving problems in stoichiometry in X  Science Class SMA Islam Bawari Pontianak and to explain cause of the errors. This research use description method with study case. The subjects of this research are twenty three students in X Science Class. Test and instrument used to collect the data are  question test and interview with students. The question test  use essay test. According to data analysis,  the result of this research showed us that students errors to understand essential concepts (24,81%), errors in comprehend contact between concepts (69,20%) and errors when using concept to solve problems (69,20%). The reason of the errors are internal factors. The internal factors that cause students errors when solving problem in stoichiometry included inablity to understand concepts in stoichiometry, poorly trained basic skills of mathematics and careless in solving problems.    Keyword: Cause of the Errors, Description, Errors, Stoichiometry.